Molecular cloning, expression and IgE-immunoreactivity of phospholipase A1, a major allergen from Polybia paulista (Hymenoptera: Vespidae) venom - Perez-Riverol, Amilcar [UNESP] (2016)
Polybia paulista (Hymenoptera: Vespidae) is a clinically relevant social wasp that frequently causes stinging accidents in southeast Brazil. To date, diagnosis and specific immunotherapy (SIT) of allergy are based on the use of crude venom extracts. Production of recombinant forms of major allergens from P. paulista venom will improve diagnosis and SIT of allergic patients by reducing the incidence of cross-reactivity and non-specific sensitization. Here, we describe the molecular cloning, heterologous expression, purification and IgE-mediated immunodetection of phospholipase A1 (Poly p 1), a major allergen from P. paulista venom. The cDNA of Poly p 1 was extracted from venom glands and then cloned, and further expression of the recombinant allergen (rPoly p 1) was achieved in Escherichia coli BL21 (DE3) cells. Purification of rPoly p 1 was performed using immobilized Ni2+ metal affinity chromatography. Also, a single-step chromatographic method allowed the purification of native Poly p 1 (nPoly p 1) from the wasp's venom glands. We used western blotting to evaluate IgE-reactivity of the sera from 10 P. paulista venom-allergic patients to rPoly p 1 and nPoly p 1. High levels of insoluble rPoly p 1 were obtained during heterologous expression. After solubilization of inclusion bodies and purification of the recombinant protein, a unique band of ∼34 kDa was detected in SDS-PAGE analysis. Allergen-specific IgE (sIgE) from allergic patients' sera recognized rPoly p 1, nPoly p 1 and crude venom extract to a similar extent. Our results showed that rPoly p 1 could be used for development of component-resolved diagnosis (CRD) and molecular-defined SIT of P. paulista venom allergy.